PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, PREFERENSI RISIKO EKSEKUTIF, DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE PERUSAHAAN SEKTOR PERTANIAN DAN PERTAMBANGAN YANG TERDAFTAR DI BEI - Dessy, Dessy; Kamaludin, Kamaludin; Nikmah, Nikmah (JURNAL FAIRNESS, 2018)
This study aims to find empirical evidence on the influence of corporate social responsibility disclosure, executive risk preference and capital intensity against tax avoidance. population in this study are all companies of agriculture and mining sector listed in BEI year 2013-2016. The type of research used in this study is empirical research. The sampling technique used is purposive sampling. Based on sampling through purposive sampling, then obtained as many as 14 samples of banking companies with a total observation of research as much as 56 observations. The results of this study found that disclosure of corporate social responsibility, executive risk preference and capital intensity did not affect tax avoidance.